2013
DOI: 10.1073/pnas.1312788110
|View full text |Cite
|
Sign up to set email alerts
|

Protein recognition and selection through conformational and mutually induced fit

Abstract: Protein-protein interactions drive most every biological process, but in many instances the domains mediating recognition are disordered. How specificity in binding is attained in the absence of defined structure contrasts with well-established experimental and theoretical work describing ligand binding to protein. The signaling protein calmodulin presents a unique opportunity to investigate mechanisms for target recognition given that it interacts with several hundred different targets. By advancing coarsegra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
97
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 53 publications
(99 citation statements)
references
References 41 publications
2
97
0
Order By: Relevance
“…It is expected that different targets are able to select the most suitable ways to bind to CaM, benefiting from the multispecificity binding. There has been increasing evidence recently to support our proposal (40,47,58,59). The experiment has shown that CaM selects the partly rather than entirely compact structure to embrace the peptide, followed by conformational adaption to the bound structure induced by peptide.…”
Section: Multispecificity Camentioning
confidence: 55%
See 1 more Smart Citation
“…It is expected that different targets are able to select the most suitable ways to bind to CaM, benefiting from the multispecificity binding. There has been increasing evidence recently to support our proposal (40,47,58,59). The experiment has shown that CaM selects the partly rather than entirely compact structure to embrace the peptide, followed by conformational adaption to the bound structure induced by peptide.…”
Section: Multispecificity Camentioning
confidence: 55%
“…This leads to a mixture of the two conventional binding scenarios (40). A mutually induced-fit scenario for binding between CaM and CaMKI peptide was proposed for CaM and CaMKI peptide (58,59), which is essentially a simultaneous binding-folding mechanism and is different from our mixture mechanism for the skMLCK. iv) It is expected that different targets can select the most suitable ways to bind to CaM, according to their structural features.…”
Section: Multispecificity Camentioning
confidence: 88%
“…Its two globular domains are connected by a flexible linker, each containing a pair of EF-hand motifs to accommodate the reversible binding of four total Ca 2ĂŸ ions (13). CaM exists as an ensemble of conformers (14)(15)(16) fluctuating around a large flat energy minimum, where conformational sampling permits a continuum of structures with similar energies (17)(18)(19)(20). CaM function depends on dynamics occurring on various spatial scales, where backbone dynamics have been shown to drive Ca 2ĂŸ affinity (13) and accommodation of a target requires large rearrangements of its domains (21).…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, we propose that TRP3 interacts with the micelles via conformational selection, i.e., the bound conformation is already present in the free ensemble and the equilibrium between conformations is re-established upon binding (52)(53)(54)(55)(56).…”
Section: Resultsmentioning
confidence: 99%